﻿Checklist of the diatoms (Bacillariophyta) from Lake Naivasha, Kenya, with some historical notes - Christine Cocquyt; Dirk Verschuren (PhytoKeys, 2023)
Lake Naivasha is one of only two large freshwater lakes in the Eastern Rift Valley of Kenya, East Africa. Together with its satellite lakes Crescent Island Crater, Oloidien and Sonachi, it comprises a great variety of pelagic and benthic habitats for aquatic biota, and its sediment record represents a unique archive of past climate change and long-term ecosystem dynamics in equatorial East Africa. This is particularly so because local paleoenvironmental reconstructions can be checked against historical data on the composition of aquatic fauna and flora collected in Lake Naivasha since the early 20th century. Some of the most prominent biological proxies for reconstructing past changes in lakes are diatoms (Bacillariophyta), a group of unicellular autotrophic eukaryotes of which the siliceous skeletons (valves) preserve well in lake sediments and are good indicators for, among others, climate-driven changes in salinity. However, diatom taxonomy and species concepts have changed a lot in recent decades, making it sometimes difficult for non-taxonomists to know which species are concerned in different published studies. This paper provides the currently accepted taxonomic names of the 310 specific and infraspecific diatom taxa reported from Lake Naivasha and its satellite lakes to date, together with their synonyms used in literature concerning these lakes as well as other, commonly used synonyms. Further, a short overview is given of the history of diatom research conducted on materials from Lake Naivasha and its satellite lakes. The present checklist may facilitate the identification and interpretation aspects of future diatom studies on the wider Lake Naivasha ecosystem and on other East African lakes that are less well studied.